Ajaran Jihad dalam Kurikulum Pesantren: Studi Kasus di Pondok Pesantren Al-Islah Bondowoso: The Teachings of Jihad in the Pesantren Curriculum: A Case Study at Al-Islah Islamic Boarding School, Bondowoso - Safrudin Edi Wibowo (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2014)
As an Islamic educational institution, the role of Islamic boarding schools (pesantren) has been re-questioned following the emergence of numerous acts of terrorist violence in Indonesia, some of which were perpetrated by individuals who admitted to being graduates of such schools. These institutions are labeled as breeding grounds for terrorism due to their curriculum, which allegedly teaches jihad ideology that legitimizes violence. This stigmatization requires further analysis to objectively present the understanding of jihad within the pesantren world. This article is the result of research conducted at Al-Islah Islamic Boarding School in Dadapan Village, Grujugan District, Bondowoso Regency. Sebagai lembaga pendidikan Islam, peran pesantren mulai dipertanyakan kembali sejak munculnya berbagai aksi kekerasan terorisme di Indonesia, di mana sebagian pelakunya mengaku sebagai lulusan pesantren. Lembaga ini ditandai sebagai tempat berkembangnya terorisme karena kurikulumnya mengajarkan ideologi jihad yang melegalkan kekerasan. Stigmatisasi tersebut perlu dianalisis lebih lanjut agar paham jihad dalam dunia pesantren dapat ditampilkan secara objektif. Artikel ini merupakan hasil penelitian yang dilakukan di Pondok Pesantren Al-Islah, Desa Dadapan, Kecamatan Grujugan, Kabupaten Bondowoso.